NUTRITIONAL PROFILE AND ITS CORRELATION WITH THE MAIN PROGNOSTIC FACTORS IN WOMEN WITH BREAST CANCER UNDERGOING SURGICAL TREATMENT - Cunha, Tamires Regina da Silva; Santiago, Isabel Cristina de Almeida; Motta, Rachel Souza Thompson (Mastology, 2018)
Objective: To analyze the association of nutritional status and fasting blood glucose with the main tumor prognostic factors in invasive breast cancer in women undergoing surgical treatment. Methods: Retrospective study with women aged 18 years or older, diagnosed with invasive breast cancer, admitted for surgical treatment at Cancer Hospital III – National Cancer Institute José Alencar Gomes da Silva. The variables collected were: age, Body Mass Index (BMI), comorbidities (hypertension and diabetes mellitus), neoadjuvant chemotherapy, menopausal status, fasting blood glucose, clinical staging, and tumor markers (estrogen and progesterone receptor/HER2/Ki-67). Categorical data were expressed by frequency and percentage, and numerical data by mean and standard deviation. We used the following tests to perform the statistical analysis: Kruskal-Wallis, Mann-Whitney, Pearson’s χ2, and Spearman tests. P-values <0.05 were considered statistically significant. Results: 166 patients participated in the study. The mean age was 59.1 (±12.4) years, and the mean fasting blood glucose was 109.5±23.7 mg/dL. According to BMI, 62.1% of the sample was overweight. The high BMI was related to hypertension and hyperglycemia, and no association with prognostic factors was found. Hyperglycemia was associated with more advanced age, higher lymph node involvement, hormone receptor positive, and post-menopausal status. Conclusion: The nutritional status classified by BMI was not related to prognostic factors in breast cancer, suggesting the need for other complementary anthropometric methods for better nutritional diagnosis.